Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1046/j.1365-2982.2000.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow transit constipation: a model of human gut dysmotility. Review of possible aetiologies

Abstract: Slow transit constipation is a severe condition of gut dysmotility that predominantly affects young women and may result in surgical intervention. Current medical treatments for STC are often ineffective, and the outcome of surgery is unpredictable. STC was first described almost a century ago. Since this time, progress in improving therapy for this condition has been complicated by a lack of understanding of the aetiology, and great variation in the methods and criteria used for the study of patients with thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
83
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(84 citation statements)
references
References 166 publications
1
83
0
Order By: Relevance
“…A reduction in ICC density has been implicated in human dysmotility syndromes including slow transit constipation (He et al 2000;Knowles and Martin 2000), chronic idiopathic intestinal pseudo-obstruction (Isozaki et al 1997), megacolon (Faussone-Pellegrini et al 1999), Chagasic megacolon (Hagger et al 2000) and ulcerative colitis (Rumessen 1996). A significant reduction in ICC density has been found in horses with grass sickness (Hudson et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in ICC density has been implicated in human dysmotility syndromes including slow transit constipation (He et al 2000;Knowles and Martin 2000), chronic idiopathic intestinal pseudo-obstruction (Isozaki et al 1997), megacolon (Faussone-Pellegrini et al 1999), Chagasic megacolon (Hagger et al 2000) and ulcerative colitis (Rumessen 1996). A significant reduction in ICC density has been found in horses with grass sickness (Hudson et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Slowtransit constipation (STC), for example, is one of many different types of constipation that is known to occur when the normal transit of colonic contents is impaired, leading to a buildup or blockage of fecal content in the large bowel (3,5,12,13,33). A number of studies have made attempts to identify mechanisms underlying the onset of STC, but no clear underlying mechanism has yet been determined.…”
mentioning
confidence: 99%
“…Female sex hormones have been suggested as possible etiologic factors in the pathogenesis of slow-transit constipation (STC) because of the higher incidence of constipation in young women than in men (29,35) as well as during the last two trimesters of pregnancy, when the levels of progesterone (P 4 ) are highest (2,5,11,13,26,28,42). This type of constipation correlates with prolonged gastrointestinal transit time (14,22). Some studies have also shown that colonic transit time is longer during the luteal phase than during the follicular phase of the menstrual cycle (1,39,40).…”
mentioning
confidence: 99%